Residual stress and deformation of welded T-joint between low carbon steel and stainless steel - Duong, Nguyen Tien (Vietnam Journal of Mechanics, 2024)
The welded structures between carbon steel and stainless steel are widely used in many sectors such as pedestrian bridges, food industry, chemical industry, petroleum, and thermal power plants, … These composite structures take advantages of each material for different parts of structure. In the welded structures between carbon steel and stainless steel, the structure is made by T-joint that is the most common. The calculation of residual stress and welding strain of the T-joint between low-carbon and stainless steel materials is the basis to evaluate the working ability of this structure. In this study, the residual stress and welding deformation of the T-joint are determined by the imaginary force method. The double-sided weld of T-joint between low carbon steel and stainless steel is welded simultaneously by MIG welding process. The obtained results of residual stress and welding deformation in this case are compared with the case of single-sided weld so that we can find the difference between residual stress and welding deformation in two cases.